Pasture brome and perennial ryegrass characteristics that influence ewe lamb dietary preference during different seasons and periods of the day - García-Favre J; Cranston LM; López IF; Poli CHEC; Donaghy DJ; Caram N; Kemp PD (Elsevier BV on behalf of the Animal Consortium, 2023)
Under the current scenario for climate change, Bromus valdivianus Phil. (Bv), a drought-resistant species, is an option to complement Lolium perenne L. (Lp) in temperate pastures. However, little is known about animal preference for Bv. A randomised complete block design was used to study ewe lamb's preference between Lp and Bv during morning and afternoon grazing sessions in winter, spring, and summer by assessing the animal behaviour and pasture morphological and chemical attributes. Ewe lambs showed a higher preference for Lp in the afternoon in winter (P < 0.05) and summer (P < 0.01), while no differences were found in spring (P > 0.05). In winter, Bv, relative to Lp, had both greater ADF and NDF (P < 0.001), and lower pasture height (P < 0.01) which negatively affected its preference. The lack of differences in spring were due to an increase in ADF concentration in Lp. In summer, ewe lambs showed the typical daily preference pattern, selecting Lp in the morning to ensure a greater quality and showing no preference during the afternoon to fill the rumen with higher fibre content. In addition, greater sheath weight per tiller in Bv could make it less desirable, as the decrease in bite rate in the species was likely due to a higher shear strength and lower pasture sward mass per bite which increased foraging time. These results provided evidence on how Bv characteristics influence ewe lamb's preference; but more research is needed on how this will affect preference for Lp and Bv in a mixed pasture
Keywords: Ewe behaviour; Food choice; Forage; Nutritive value; Selective grazing; Female; Sheep; Animals; Lolium; Bromus; Seasons; Animal Feed; Diet; Sheep, Domestic